Mother tongue-based Multilingual Education in Bihar: A Practical Approach - Raaj, Shilpy (IJRDO- Journal of Educational Research, 2017)
Research has shown a positive correlation between multilingual language proficiency andacademic achievement by emphasising that multilingualism leads to greater cognitive flexibilityand social tolerance. Some studies in India have undertaken empirical research to prove this butnot much has been done in the state of Bihar despite having a rich repertoire of languages andfirm language policies in place. There is a need of weaving theory with practice so that themultilingual classrooms in Bihar can actually be developed as a resource and children do notfeel marginalised merely on account of language. This would go a long way in mainstreamingthe linguistic minority children and preventing indigenous languages from dying out. Issues suchas these provided the rationale for writing this paper which aims at bridging the gap between thepolicies and their actual implementation in the classrooms by giving some recommendations atthe end.